Determinación de bacterias de interés clínico en productos agrícolas con riego del río Chibunga - Edwin Dario, Chicaiza Guanoluiza (2019)
Antimicrobial resistance has become an emerging global obstacle, thus proclaiming one of the most serious today. The mutagenic alteration and natural evolution of the bacteria have caused multi-resistance to various antibiotics. The present study aims to determine the presence of pathogenic bacteria in agricultural products irrigated by the Chibunga River. Human pathogenic bacteria, causing gastrointestinal infections, were isolated and identified. It is a descriptive, cross-sectional cohort study with a field design. Sample collection began at six geographical sampling points, including the measurement of altitude and ambient temperature. In the isolation and purification of colonies, McConkey and Blood agar were used for the identification of bacteria classified in gender and species, chemical and physiological tests were used. Bacterial resistance and susceptibility were measured by the agar diffusion technique, Kirby Bauer. The acquired results show eight pathogenic bacteria, which corresponds to 7 Gram-negative; such as Citrobacter amalonaticus, Citrobacter freundii, Enterobacter cloacae, Klebsiella pneumonia, Plesiomona shigelloides, Morganela morganni, Aereomona sobria and exclusively 1 Gram-positive: Enterococcus faecalis. 25% of the isolated bacteria showed resistance against cephalosporins, and another 25% of the total microorganisms found showed resistance to beta-lactamase and glycopeptides. Evidence of the contamination that exists in the Chibunga River, with multiresistant bacteria to various antibiotic lines for clinical use.